Analysis of Sirolimus Blood Concentration and Influencing Factors in Pediatric Patients: Implications for Individualized Drug Therapy - Xiaolin Xu; Xueting Mao; Bo Liu; Yixin Sun; Xiaoling Cheng; Xiaoling Wang; Huawei Mao (Drugs in R&D)
Abstract Background and Objective The purpose of this study is to investigate the status of blood concentration of sirolimus (SRL), explore the factors influencing SRL drug blood concentration, and provide guidance for the appropriate utilization of clinical medications. Methods A single-center retrospective cohort study encompassed 1535 blood drug concentration observations obtained from 249 children from August 2018 to June 2023. Participants were categorized into four groups (A, B, C, and D) on the basis of their blood concentration levels at various time intervals. The analysis focused on identifying the factors that influenced blood concentration in the short- and long-term posttreatment. The primary endpoint was factors affecting the sirolimus blood concentration. The effect of physiopathological indicators on the corrected blood drug concentration (C/D value) was analyzed to avoid the effect of differences in the dose of SRL used in patients on SRL blood concentrations. The multiple linear regression model was used to examine the impact of factors influencing pharmacokinetics and pharmacodynamics on the C/D. Results Analysis of SRL blood concentration monitoring indicated that a majority (60.43%) of patients demonstrated a trough sirolimus concentration (C 0) below the level of the recommended threshold of 5 ng/mL, while approximately 17.7% of patients exceeded 15 ng/mL. The results indicated a noteworthy association between weight and body surface area (BSA) and the C/D of SRL in groups A, B, and D (P < 0.05). Additionally, aspartate transaminase (AST), alanine aminotransferase (ALT), and albumin (ALB) in group A; ALB in group B; and platelet count (PLT) in group C demonstrated a statistically significant correlation with the C/D of SRL (P < 0.05). Conclusions Clinicians should optimize medication plans by considering the child’s weight, BSA, ALT, AST, PLT, ALB, and relevant factors. These findings may serve as a valuable resource for clinicians.